2006
DOI: 10.1192/bjp.bp.105.015412
|View full text |Cite
|
Sign up to set email alerts
|

Use of standardised outcome measures in adult mental health services

Abstract: Routine use of outcome measures as implemented in this study did not improve subjective outcomes, but was associated with reduced psychiatric inpatient admissions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(87 citation statements)
references
References 30 publications
3
81
0
2
Order By: Relevance
“…This also applies to potential cost savings. The FOCUS study 16 mentioned previously suggested that annual cost savings of regular outcome data feedback (which is also provided in DIALOG) was equivalent to £5172 per patient through reduced bed use. If replicated for only 20% of patients with schizophrenia and related disorders in community care in the NHS, the savings would exceed £100M every year.…”
Section: The Dialog Interventionmentioning
confidence: 99%
“…This also applies to potential cost savings. The FOCUS study 16 mentioned previously suggested that annual cost savings of regular outcome data feedback (which is also provided in DIALOG) was equivalent to £5172 per patient through reduced bed use. If replicated for only 20% of patients with schizophrenia and related disorders in community care in the NHS, the savings would exceed £100M every year.…”
Section: The Dialog Interventionmentioning
confidence: 99%
“…Regular outcome assessments have been linked to improvements in service delivery and lower readmission rates 103 , whereas infrequent outcome measurement did little to improve quality 104 . Moreover, routine outcome measurement that was fed back to the clinician and used to make joint treatment decisions with the patient did lead to better quality of life 105 .…”
Section: Recommendationsmentioning
confidence: 99%
“…Two approaches to ROA should be distinguished: one in which the outcome assessments take place outside client-clinician contacts (see, e.g., Marshall et al, 2004;Slade et al, 2006) and one in which they are incorporated into 'routine' client-clinician contacts (see, e.g., Priebe et al, 2007;Van Os et al, 2004). We modeled our routine violence risk assessment method after the latter approach, because this approach showed positive short term effects on client-clinician communication and treatment (Van Os et al, 2004) and long term improvements in client satisfaction, quality of life, and needs for care (Priebe et al, 2007).…”
Section: Introductionmentioning
confidence: 99%